Animal evolution genomes, fossils, and trees - Telford, Maximilian J.; Littlewood, D. T. J. (D. Timothy J.), 1961- (Oxford : Oxford University Press, 2009)
Describing and understanding the evolution of the diversity of bodyplans is a major goal of evolutionary biology. Taking a modern, integrated approach to this question, a group of researchers describe how modern techniques and disciplines have been combined, resulting in a dramatic renaissance in the study of animal evolution.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Phylogeny; Evolution (Biology)